Night illumination (Pacific Novelty Co.)
On verso: The lighting reaches a point of perfection never before accomplished on such an extensive scale. On the bay shore is placed a "scintillator"comprising forty-eight powerful searchlights manned by as many operators specially trained for the work. At night when these powerful rays of light are sent forth with ever-changing rainbow colors over the buildings and into the fleecy clouds or fog banks, it is a spectacle entrancing to old and young alike.